Diagnostic utility of fecal calprotectin as a biomarker of gut inflammation in neonates to predict necrotizing enterocolitis: A prospective study - Shenoy, Mohan T; Shenoy, K T; Roseth, A; Geir, Larsson; Keshavamurthy, S R (Indian Journal of Child Health, 2014)
Background: Necrotizing enterocolitis (NEC) is a neonatal emergency that affects preterm newborns during the 1st weeks of life. Diagnosis is made mainly by clinical criteria since no specific diagnostic tests are available. Objective: The objective was to evaluate fecal calprotectin (fCal) as a biomarker of gut inflammation to predict NEC in preterm neonates. Methods: Design: Diagnostic test evaluation. Inclusion criteria: 102 preterm neonates 279 ?g/g as cutoff, the area under the curve was 0.652 (95% confidence interval: 0.516-0.789). Day 3 fCal levels were high in 65.7% neonates. Using NEC as outcome, sensitivity of the test was 93.3%; specificity was 39%; positive predictive value was 20.8% and negative predictive value was 97.14%. Conclusion: fCal has high sensitivity for diagnosing NEC in preterm neonates. However, further research is needed to establish its clinical usefulness.